Impact of the Iranian Registry of Infective Endocarditis (IRIE) and multidisciplinary team approach on patient management. Issue 8 (10th November 2021) - Sadeghpour, A.; Maleki, M.; Boodagh, Sh; Behjati, M.; Rezvani, L.; Ghadrdoost, B.; Noohi, F.; Bakhshandeh, H.; Moradnejad, P.; Kamali, M.; Alizadehasl, A.; Alireza Ghavidel, A.; et al.
Abstract: Backgrounds: The last 30 years have witnessed major improvements in understanding of all aspects of infective endocarditis (IE). The Iranian Registry of Infective Endocarditis (IRIE) was formed to address epidemiological aspects of IE vis-à-vis its main pathogens and underlying heart diseases over a 12-year period. Indeed, a multidisciplinary team (MDT) for IE was developed alongside. Methods: In a longitudinal observational study, data of adult patients with definite or possible IE based on modified Duke criteria were collected from 2007 to 2016 in our tertiary centre, Iran. From 2016 until 2019, we run a prospective observational study using formation of an IE MDT to provide better patient management and compared data before and after this. Results: Totally, 645 patients with mean age of 48 ± 17 years were enrolled. Data of 445 and 200 patients were compared before and after IRIE and MDT formation, respectively. We found significantly reduced type and number of applied antibiotics ( p = 0.04) and higher rate of positive blood culture ( p = 0.001). Hospital length of stay increased significantly after formation of the IRIE and IE MDT ( p = 0.02). The rate of heart failure, new abscess formation and cerebral emboli were significantly decreased after IRIE and IE MDT ( p < 0.001) and consequently in-hospital mortality reduced significantly ( p = 0.05). Conclusion: Developing national registries and MDTs has potential to enhance patient management and reduce IE burden. Our results demonstrated that establishment of the Iranian IRIE and IE MDT conferred better diagnoses, standardised treatments and significantly reduced cardiac and extra cardiac morbidity.